OX-1 metal–organic framework nanosheets as robust hosts for highly active catalytic palladium species - Titov, K; Eremin, DB; Kashin, AS; Boada, R; Souza, BE; Kelley, CS; Frogley, MD; Cinque, G; Gianolio, D; Cibin, G; Rudic, S; Ananikov, VP; et al. (American Chemical Society, 2019)
A catalytic system based on OX-1 metal–organic framework nanosheets is reported, incorporating catalytically active palladium (Pd) species. The Pd@OX-1 guest@host system is rapidly synthesized via a one-step single-pot supramolecular assembly, with the possibility of controlling the Pd loading. The structures of the resulting framework and of the active Pd species before and after catalytic reactions are studied in detail using a wide variety of techniques including synchrotron radiation infrared spectroscopy, inelastic neutron scattering, and X-ray absorption spectroscopy. Crystals of the resulting Pd@OX-1 composite material contain predominantly atomic and small cluster Pd species, which selectively reside on benzene rings of the benzenedicarboxylate (BDC) linkers. The composites are shown to efficiently catalyze the Suzuki coupling and Heck arylation reactions under a variety of conditions. Pd@OX-1 further shows potential to be recycled for at least five cycles of each reaction as well as an ability to recapture active Pd species during both catalytic reactions.